Speckle Noise Reduction in Fetal Ultrasound Image Using Various Filtering Techniques - Joharah, S. Fathimuthu; Mohideen, S. Kother (International Journal of Computer Sciences and Engineering, 2025)
Ultrasound imaging is widely used in medical diagnosis, because of its non invasive nature, low cost, capability of forming real time imaging and continued improvement in image quality. The main drawback during diagnosis is the distortion of visual signals. These distortions are termed as speckle noise, which makes the image unclear and make diagnostic more difficult. Many denoising techniques are proposed for effective suppression of speckle noise. In this paper three adaptive filters are used and we have compared and evaluated the performance of famous filters for speckle noise reduction in fetal ultrasound image.